The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1987
DOI: 10.1111/j.1471-4159.1987.tb00978.x
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the Dihydropyridine Binding Sites of Rat Neocortical Synaptosomes and Microvessels

Abstract: The dihydropyridine binding sites associated with rat neocortical synaptosomes and microvessels were compared using an in vitro [3H]PN 200-110 [(+)-[methyl-3H]-isopropyl 4-(2,1,3-benzoxadiazol-4-yl)-1,4-dihydro-2,6-dimethyl-5- methoxycarbonylpyridine-3-carboxylate] binding assay. Saturation experiments yielded similar KD values (approximately 70 pM) and Bmax values (approximately 400 fmol/mg of protein) for the two membrane preparations. Interaction experiments with [3H]PN 200-110 and various calcium-modulatin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

1989
1989
2002
2002

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…The increase in [Ca2+Ii in synaptosomes treated with PKC-stimulating phorbol esters also is inhibited by DHP channel blockers (Adamson et al, 1989). Furthermore, binding sites for dihydropyridines have been characterised on synaptosomes (Dooley et al, 1987), and the a2 subunit of the DHP receptor has been identified in rat brain synaptosomes using polyclonal antibodies (Sharp and Campbell, 1989).…”
Section: Discussionmentioning
confidence: 99%
“…The increase in [Ca2+Ii in synaptosomes treated with PKC-stimulating phorbol esters also is inhibited by DHP channel blockers (Adamson et al, 1989). Furthermore, binding sites for dihydropyridines have been characterised on synaptosomes (Dooley et al, 1987), and the a2 subunit of the DHP receptor has been identified in rat brain synaptosomes using polyclonal antibodies (Sharp and Campbell, 1989).…”
Section: Discussionmentioning
confidence: 99%
“…Dihydropyridine (dhp) binding sites on cerebral microvessels have similar, if not identical, pharmacological properties to neuronal dhp binding sites [3]. Nimodipine exerts a vasodilatory action by a blockade of vascular L-type calcium channels, hereby increasing cerebral blood flow [13], known to be impaired during ageing [6].…”
Section: Discussionmentioning
confidence: 99%
“…Our experiments have indicated that entry of extracellular Ca2+ through a verapamil-and nisolclipinesensitive pathway, presumably voltage-sensitive Ca2+ channels, is a prerequisite for the 1 M mannitcsl-mediated stimulation of ODC activity and the concomitant increase in 45Ca2+ influx, HRP uptake, and DG uptake. Brain microvessel membranes possess voltagesensitive Ca2+ channels, as identified by high-affinity dihydropyridine binding sites, that are identical to those present in neocortical synaptosomal membranes (Dooley et al, 1987). Extracellular Ca2+ is required for the induction of ODC activity in cultured cells by a number of agonists.…”
Section: Discussionmentioning
confidence: 99%